2003
DOI: 10.1139/v03-133
|View full text |Cite
|
Sign up to set email alerts
|

Hydrosilylation of alkenes and ketones catalyzed by nickel(II) indenyl complexes

Abstract: Abstraction of Cl– from the complexes (indenyl)Ni(PPh3)Cl generates cationic species that are effective precatalysts for the hydrosilylation of some olefins and ketones. For instance, the mixture of (1-Me-indenyl)Ni(PPh3)Cl and NaBPh4 (or methylaluminoxane) reacts at room temperature with ca. 100 equiv. each of PhSiH3 and styrene to produce [1-phenyl-1-ethyl](phenyl)silane, PhCH(CH3)(SiPhH2), in 50%–80% yield. The same system can also catalyze the hydrosilylation of 1-hexene and norbornene, but the products ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 12 publications
2
39
0
1
Order By: Relevance
“…Therefore, it is to be noted that the reaction catalyzed by the (salicylaldiminato)Ni(II)methyl complex would be one of the rare examples of a Ni‐catalyzed hydrosilylation that follows the metathesis mechanism 22. This could be one reason for the good reaction selectivity and rather wide substrate scope of this system.…”
Section: Mechanistic Investigationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, it is to be noted that the reaction catalyzed by the (salicylaldiminato)Ni(II)methyl complex would be one of the rare examples of a Ni‐catalyzed hydrosilylation that follows the metathesis mechanism 22. This could be one reason for the good reaction selectivity and rather wide substrate scope of this system.…”
Section: Mechanistic Investigationsmentioning
confidence: 98%
“…It was indicated that the stoichiometric reaction of 1a with Ph 2 SiH 2 resulted in the formation of silyl complex A based on 1 H and 29 Si NMR spectroscopies. Because a Chalk–Harrod or modified Chalk–Harrod‐type mechanism via Ni(II)/Ni(IV) intermediates is less likely,21,22b we proposed a metathesis mechanism for this system (Scheme ) 12. Complex 1 initially reacts with the hydrosilane to give silyl intermediate A , which further undergoes successive alkene coordination and insertion to give C via B .…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…(1-MeInd)Ni(PPh 3 )Cl, which had previously been studied as acatalyst for dehydropolymerzation of phenylsilane, [98] can be used as ac atalyst for the hydrosilylation of styrene with phenylsilane with 2mol %catalyst loading. [99] Te thered amino complex 141 displays longer catalytic lifetimes and as little as 1mol %o ft his complex can be used to give aq uantitative yield of the a-silylated product 142 as the sole regioisomer (Scheme 48). [100] Thet ethered ligand prevents catalyst deactivation via decomposition to an unknown number of nickel complexes.A lternatively,b ulky indenyl complexes [1,3-(TMS) 2 Ind]Ni(PPh 3 )Cl) [101] can be used instead of 141 to deliver 142 in an 82 %yield.…”
Section: Nickel and Palladiummentioning
confidence: 99%
“…Im Vergleich zu anderen Übergangsmetallen sind die katalytischen Eigenschaften von Indenylnickel‐ und Indenylpalladiumkomplexen im Zusammenhang mit der organischen Synthese wenig erforscht. (1‐MeInd)Ni(PPh 3 )Cl, das zuvor als Katalysator für die Dehydropolymerisierung von Phenylsilan untersucht wurde, katalysiert in einer Menge von 2 Mol‐% die Hydrosilylierung von Styrol mit Phenylsilan . Der Komplex 141 mit angebundener Amin‐Donorgruppe ist ein Katalysator mit längerer Lebensdauer, und mit nur 1 Mol‐% dieses Komplexes wird in quantitativer Ausbeute das α‐silylierte Produkt 142 als einziges Regioisomer erhalten (Schema ) .…”
Section: Nickel Und Palladiumunclassified